The application of critical thinking in the process of jarḥ wa-taʿdīl in the science of ḥadīth - Abdullah, Ismail (Intellectual discourse, 2012)
The process of critical thinking could be employed in evaluating the strength and weakness of any argument. As regards jarḥ wa-taʿdīl (impugnment and validation), muḥaddithūn (scholars of ḥadīth) examine the reliability and trustworthiness of the transmitters to establish the acceptability of their report as being attributed to Prophet Muhammad (s.a.w.). Jarḥ wa-taʿdīl, which constitutes the criticism of the chain of transmitters and textual criticism, is regarded as the first part of ḥadīth criticism. This study analyses the elements of critical thinking in differentiating between fact and opinion, author bias rhetoric, comparing and contrasting, judgment and logical conclusion, etc., whereby these elements are crucial to determine the reliability and trustworthiness of narrators of ḥadīth. Moreover, it discusses the application of these techniques as propounded by the muḥaddithūn in jarḥ wa-taʿdīl.